Exchange rate misalignment and its effects on agricultural producer support estimates: empirical evidence from India and China - Cheng, Fuzhi; Orden, David (International Food Policy Research Institute, 2005)
There have been different degrees of exchange rate disequilibrium in the developing countries during transition or reform periods since the mid 1980s. The level of the exchange rate and its misalignment can have significant impacts on agricultural policy measures such as Producer Support Estimates (PSEs). In the conventional PSE analysis, however, the actual (nominal) exchange rates are used. There is general agreement that the use of actual exchange rates may introduce a bias in the PSE calculations, and that this bias can be substantial in some cases. But there is less agreement on the most appropriate alternative. In this study, we utilize various time series techniques to derive estimates of the equilibrium exchange rates in India and China from the 1970s to 2002 as determined by real economic fundamentals. The relevance and usefulness of the equilibrium exchange rates in the calculation of PSE for the two countries are then discussed. Drawing on the data sets and analyses developed earlier by Mullen, Orden and Gulati (2005) and Sun (2003), we find that agricultural support levels measured by the PSEs (from 1985-2002 for India and from 1995-2001 for China) are sensitive to alternative exchange rate assumptions. Specifically, exchange rate misalignments have either amplified or counteracted the direct effects from sectoral-specific policies. In India, such indirect effects are relatively small and mostly dominated by the direct effects. But in China, especially in recent years, the indirect effect from exchange rate misalignment (undervaluation) has been quite substantial. Results from this study also show that the effect of the exchange rate depends on the relative importance of different PSE components. The increasing share of budgetary expenditures in India’s total agricultural support in recent years has resulted in more pronounced exchange rate effects measured by commodity-specific percentage “PSEs” that use the value of production at international prices as the denominator compared to those measured by commodity-specific percentage Market Price Support (MPS) with the same denominator. For China, the exchange rate effects are more similar between the PSE and the MPS measures because budgetary expenditures have been relatively small. The exchange rate effect when the PSE is “scaled up” from covered commodities to an estimate for the total agricultural sector is also demonstrated. Since the commodity coverage in both countries tends to be incomplete and the scaling-up procedure leads to a total MPS of greater magnitude, larger exchange rate effects are found in the scaled-up than the non-scaled-up version of total PSEs. The impact of scaling-up on the indirect effect is proportional to the share of covered commodities in the total value of agricultural production.